A data-driven approach to improve wellness and reduce recurrence in cancer survivors - Hariharan, Ramkumar; Hood, Leroy; Price, Nathan D. (Frontiers in Oncology, 2024)
For many cancer survivors, toxic side effects of treatment, lingering effects of the aftermath of disease and cancer recurrence adversely affect quality of life (QoL) and reduce healthspan. Data−driven approaches for quantifying and improving wellness in healthy individuals hold great promise for improving the lives of cancer survivors. The data-driven strategy will also guide personalized nutrition and exercise recommendations that may help prevent cancer recurrence and secondary malignancies in survivors.